COVID-19 Vaccine Boosters: Rationale, Efficacy, and Implementation Strategies - Bilegtsaikhan Tsolmon (Pacific International Journal, 2023)
The development of COVID-19 vaccines has been a major milestone in controlling the pandemic. However, with the emergence of SARS-CoV-2 variants and the potential for waning immunity, vaccine booster doses have become an essential consideration for maintaining vaccine effectiveness. In this review, we discuss the rationale for COVID-19 vaccine boosters, evidence of their efficacy, and implementation strategies. We also explore the challenges of global booster dose distribution and potential futureresearch directions.